3‐D Modeling of Ultrathin Solar Cells with Nanostructured Dielectric Passivation: Case Study of Chalcogenide Solar Cells (Adv. Theory Simul. 11/2021). Issue 11 (8th November 2021) - Raja, Waseem; Aydin, Erkan; Allen, Thomas G.; De Wolf, Stefaan
Abstract : 3‐D Modeling of Ultrathin Solar Cells In article number 2100191, Waseem Raja, Erkan Aydin, Thomas G. Allen, and Stefaan De Wolf develop a novel 3‐D optoelectrical finite‐element model to analyze the performance of ultrathin solar cells. In particular, the 3‐D model investigates the light trapping and field passivation in which the negative charges induced on the nanostructured passivation layer repel the minority charge carriers, increasing the solar cell's open‐circuit voltage and power conversion efficiency.